Long Island compromise : [large type] a novel - Brodesser-Akner, Taffy (Random House Large Print, 2024)
"In 1983, a wealthy businessman named Carl Fletcher is kidnapped from his driveway in the nicest part of Long Island, brutalized, and held for ransom. He is returned to his wife and kids less than a week later, only slightly the worse for wear, and the family begins the hard work of trying to move on with their lives and resume their prized places in the saga of the American dream, coming to understand that though their money may have been what put them in danger, it is also what guaranteed them their safety in the end. But forty years later, when Carl's mother dies and the family comes home to mourn her, it becomes clear that nobody ever really got over anything. Carl's wife, Ruth, has spent her potential protecting her husband's emotional health. Their three grown children are each a mess: Nathan cannot seem to advance at his law firm and may have made a terrible investment with his trust fund; Beamer, a Hollywood screenwriter, will consume anything--substance, foodstuff, women--in order to numb his own perpetual terror; and Jenny has spent her life so bent on proving that she is not a product of the family's pathology that she comes to define it. Then there's Carl himself, the prickly, still-terrified father, who has been secretly seeking closure to the matter of his kidnapping for years, and the unthinkable act he commits that will alter the family's path forever"--